Pestman Enterprise : "Super Sprayer" / Muhammad Fahim Basri...[et.al] - Basri, Muhammad Fahim; Radzali, Mohd Zulhazwan; Azmi, Muhammad Azwan; Mohd Amin, Muhammad Amirul (Faculty of Plantation and Agrotechnology, 2015)
Pestman Enterprise is a privately possessed innovation item organization that will make our organization is an entrenched organization as other contender through our extraordinary and brilliant showcasing technique of our organization. Pestman Enterprise will deliver another innovation item at reasonable cost. This business depends on partnership which is including of five members. The individuals comprise of General Manager, Administration Manager, Operational Manager, Marketing Manager and Financial Manager.